Novel Drug Delivery Systems as an Emerging Platform for Stomach Cancer Therapy - Umme Hani; Riyaz Ali M. Osmani; Sabina Yasmin; B. H. Jaswanth Gowda; Hissana Ather; Mohammad Yousuf Ansari; Ayesha Siddiqua; Mohammed Ghazwani; Adel Al Fatease; Ali H. Alamri; Mohamed Rahamathulla; M. Yasmin Begum; et al. (MDPI AG, 2022)
Cancer has long been regarded as one of the world's most fatal diseases, claiming the lives of countless individuals each year. Stomach cancer is a prevalent cancer that has recently reached a high number of fatalities. It continues to be one of the most fatal cancer forms, requiring immediate attention due to its low overall survival rate. Early detection and appropriate therapy are, perhaps, of the most difficult challenges in the fight against stomach cancer. We focused on positive tactics for stomach cancer therapy in this paper, and we went over the most current advancements and progressions of nanotechnology-based systems in modern drug delivery and therapies in great detail. Recent therapeutic tactics used in nanotechnology-based delivery of drugs aim to improve cellular absorption, pharmacokinetics, and anticancer drug efficacy, allowing for more precise targeting of specific agents for effective stomach cancer treatment. The current review also provides information on ongoing research aimed at improving the curative effectiveness of existing anti-stomach cancer medicines. All these crucial matters discussed under one overarching title will be extremely useful to readers who are working on developing multi-functional nano-constructs for improved diagnosis and treatment of stomach cancer.